Striving for authenticity the foundation and dynamics of the AlDub Nation fandom - Cabbuag, Samuel (2023)
Access online through this link: https://www.plarideljournal.org/article/striving-for-authenticity-the-foundation-and-dynamics-of-the-aldub-nation-fandom
Keywords: Romance in television; Richards, Alden; Mendoza, Maine; Fan studies; Television viewers